RANCANG BANGUN PERANGKAT LUNAK UNTUK PERHITUNGAN SEL DARAH MERAH NORMAL DAN TERINFEKSI MALARIA - Setyowati, Setyowati; Adi, Kusworo; Anam, Choirul (BERKALA FISIKA, 2019)
Malaria is a serious global health problem. Calculation of normal and malaria-infected red blood cells is manually calculated on image of the blood taken by the light microscope. The calculation of the normal and the malaria-infected red blood cells is to know the percentage of parasites and their growth. In addition, it was used to determine the percentage of inhibition parasite growth. The aim of this study is to automatically calculate a total, normal and malariainfected red blood cells. The steps for the calculation of the total of red blood cells: normalization, thresholding, separation and calculation of the red blood cells by labeling. The steps of calculation of malaria-infected red blood cells: converting RGB image to grayscale and to binary image, sweeping, and the calculation of malaria-infected red blood cells. The normal red blood cells can be determined by subtracting the total of the red blood cells with the malaria-infected red blood cells. This software is able to automatically calculate the total, normal and malaria-infected red blood cells. The results of automated calculation with the developed software are not different from a manual calculation. The calculation error of the program compared to the manual calculation is only one or two of the red blood cells for eachimage.Keywords: malaria, calculation of blood cell, infected blood cell.